2007
DOI: 10.1016/j.jmb.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Structures of MART-126/27–35 Peptide/HLA-A2 Complexes Reveal a Remarkable Disconnect between Antigen Structural Homology and T Cell Recognition

Abstract: Small structural changes in peptides presented by major histocompatibility complex (MHC) molecules often result in large changes in immunogenicity, supporting the notion that T cell receptors are exquisitely sensitive to antigen structure. Yet there are striking examples of TCR recognition of structurally dissimilar ligands. The resulting unpredictability of how T cells will respond to different or modified antigens impacts both our understanding of the physical bases for TCR specificity as well as efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 56 publications
(51 reference statements)
12
122
0
Order By: Relevance
“…Structural evidence suggests that substitution of alanine to leucine at the p2 anchor residue does not substantially alter Melan-A/MART-1 [26][27][28][29][30][31][32][33][34][35] peptide conformation in the uncomplexed pHLA A p 0201 molecule (47,48). However, a number of recent studies have shown that peptide conformation can be substantially altered during TCR docking (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Structural evidence suggests that substitution of alanine to leucine at the p2 anchor residue does not substantially alter Melan-A/MART-1 [26][27][28][29][30][31][32][33][34][35] peptide conformation in the uncomplexed pHLA A p 0201 molecule (47,48). However, a number of recent studies have shown that peptide conformation can be substantially altered during TCR docking (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we now consider modified peptides as a potential "false ally" in cancer vaccines because their increased immunogenicity does not necessarily result in enhanced antitumor T-cell reactivity. Although the level of cross-recognition may vary among peptides, the unpredictability of T-cell function (48,49) makes this approach suboptimal for the effective enhancement of tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In examining the structure of the HCV1406-NS3/A2 complex, we noted that the conformation of the NS3 peptide in the A2-binding groove is remarkably similar to the conformation of the decameric MART-1 tumor antigen (sequence ELAGIGILTV) bound to A2 (35,36) (Fig. 6A).…”
Section: Cross-reactivity With a Tumor Antigen Reveals Cooperativitymentioning
confidence: 90%